A prospective analysis of urinary tract infections among elderly trauma patients. Issue 4 (October 2015) - Zielinski, Martin D.; Kuntz, Melissa M.; Polites, Stephanie F.; Boggust, Andy; Nelson, Heidi; Khasawneh, Mohammad A.; Jenkins, Donald H.; Harmsen, Scott; Ballman, Karla V.; Pieper, Rembert
Abstract : BACKGROUND: Catheter-associated urinary tract infections (CAUTIs) have been deemed "reasonably preventable" by the Centers for Medicare and Medicaid, thereby eliminating reimbursement. Elderly trauma patients, however, are at high risk for developing urinary tract infections (UTIs) given their extensive comorbidities, immobilization, and environmental changes in the urine, which provide the ideal environment for bacterial overgrowth. Whether these patients develop CAUTI as a complication of their hospitalization or have asymptomatic bacteriuria (ASB) or UTI at admission must be determined to justify the "reasonably preventable" classification. We hypothesize that a significant proportion of elderly patients will present with ASB or UTI at admission. METHODS: Institutional review board permission was obtained to perform a prospective, observational clinical trial of all elderly (≥65 years) patients admitted to our Level I trauma center as a result of injury. Urinalysis (UA) and culture (UCx) were obtained at admission, 72 hours, and, if diagnosed with UTI, at 2 weeks after injury. Mean cost of UTI was calculated based on Centers for Disease Control and Prevention estimates of $862 to $1, 007 per UTI. RESULTS: Of 201 eligible patients, 129 agreed to participate (64%). Mean (SD) age was 81 (8.6) years. All patients had a blunt mechanism of injury (76% falls), with a mean Injury Severity Score (ISS) of 13.8 (7.6). Of the 18 patients (14%) diagnosed with CAUTI, 14 (78%) were present at admission. In addition, there were 18 patients (14%) with ASB at admission. The most common bacterial species present at admission urine culture were Escherichia coli (24%) and Enterococcus (16%). Clinical features associated with bacteriuria at admission included a history of UTI, positive Gram stain result, abnormal microscopy, and pyuria. The estimated loss of reimbursement for 18 UTIs at admission was $15, 516 to $18, 126; however, given an estimated cost of $1, 981 to screen all patients with UA and UCx at admission, up to $16, 144 savings was realized. CONCLUSION: Many elderly trauma patients present with UTI. Screening UA and UCx at admission for elderly trauma patients identifies these UTIs and is cost-effective. LEVEL OF EVIDENCE: Epidemiologic study, level II.